2018
DOI: 10.1111/papr.12677
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose Exposure for Lumbar Transforaminal Epidural Steroid Injections and Facet Joint Blocks Under CT vs. Fluoroscopic Guidance

Abstract: The study results suggest that TFESIs and facet joint blocks performed with CT guidance are associated with more than 8 times higher patient radiation dose exposure compared to fluoroscopic guidance. There needs to be more vigilance with regards to CT guidance in interventional pain procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…any patients with radicular pain due to nerve root compression or low back pain related to degeneration of the facet joint respond favorably to imaging-guided spinal therapeutic injections with steroids (1)(2)(3). Lumbar transforaminal epidural and lumbar facet joint steroid injections can be performed reliably, safely, and quickly with either a fluoroscopy-guided or CT-guided technique (4)(5)(6).…”
mentioning
confidence: 99%
“…any patients with radicular pain due to nerve root compression or low back pain related to degeneration of the facet joint respond favorably to imaging-guided spinal therapeutic injections with steroids (1)(2)(3). Lumbar transforaminal epidural and lumbar facet joint steroid injections can be performed reliably, safely, and quickly with either a fluoroscopy-guided or CT-guided technique (4)(5)(6).…”
mentioning
confidence: 99%
“…Wearing lead aprons, maximizing the distance from the radioactive source, minimizing exposure time, avoiding magnification and increasing use of collimation are the main strategies to reduce radiation exposure with respect to ALARA principle [3,12] Aforementioned recommendations are often oversight; besides, physicians need reference level standards to assure quality controls. There is paucity of data regarding reference dose standards for epidural injections and available research have been focused on comparing radiation exposure for computed tomography or fluoroscopy-guided injections or conducted with relatively small sample sizes without available reference levels [13][14][15]. Our study is inspired by the paper of Cohen et al, which assessed 6.234 spinal injections and provided reference radiation doses for eleven different interventional procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, the extra-guidance technique using the Xper CT reflected a better efficacy with a moderate increase of irradiation hazards (2 folds increase in ED). The implication of CT as a guidance tool has been used for interventional pain procedures, such as celiac plexus and lumbar sympathetic blocks [36, 37]. It allows better visualization of the whole needle path, surrounding soft tissues, and vascular and bony structures [38].…”
Section: Discussionmentioning
confidence: 99%
“…It allows better visualization of the whole needle path, surrounding soft tissues, and vascular and bony structures [38]. However, CT-associated exposure to excessive irradiation may induce carcinogenesis, genetic mutation and several other hazards [37, 38]. In previous studies conducted by Hoang et al [39] and Schmid et al [40] comparing irradiation dose during pain interventions guided by fluoroscopy versus CT, Hoang et al reported 4 times more radiation exposure during CT than fluoroscopy [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation